Enlightening enthusiasm: Prophecy and religious experience in early eighteenth-century England - Laborie, Lionel (Manchester University Press, 2015)
In the early modern period, the term "enthusiasm" was a smear word used to discredit the dissenters of the radical Reformation as dangerous religious fanatics. In England, the term gained prominence from the Civil War period and throughout the eighteenth century. Anglican ministers and the proponents of the Enlightenment used it more widely against Paracelsian chemists, experimental philosophers, religious dissenters and divines, astrologers or anyone claiming superior knowledge. But who exactly were those enthusiasts? What did they believe in and what impact did they have on their contemporaries? This book concentrates on the notorious case of the French Prophets as the epitome of religious enthusiasm in early Enlightenment England. Based on new archival research, it retraces the formation, development and evolution of their movement and sheds new light on key contemporary issues such as millenarianism, censorship and the press, blasphemy, dissent and toleration, and madness